2020
DOI: 10.1177/1558944720937369
|View full text |Cite
|
Sign up to set email alerts
|

MRI Findings in Patients Undergoing Triangular Fibrocartilage Complex Repairs Versus Patients Without Ulnar-Sided Wrist Pain

Abstract: Background: The clinical picture of ulnar-sided wrist pain is oftentimes confusing because various pathologies may be coexistent. In this study, we aimed: (1) to compare the prevalence of potential causes of ulnar-sided wrist pain on magnetic resonance imaging (MRI) in patients who underwent triangular fibrocartilage complex (TFCC) repair and control subjects: and (2) to evaluate whether inferior clinical results were associated with specific patient characteristics or other potential causes of ulnar-sided wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Zhan et al (2020) reported three patients with peripheral (Palmer 1B) TFCC injuries and additional ECU pathology but did not study the association between these findings in their small sample [ 4 ]. Verhiel et al (2020) assessed 67 patients with TFCC tears and 67 controls with MRI and arthroscopy, concluding that ECU pathology and distal radioulnar joint arthritis are associated with TFCC tears [ 15 ]. In the most recent work, Kim et al (2021) studied the ECU tendon subluxation with 297 MRI cases; out of these, 111 cases had arthroscopic evaluation of TFCC.…”
Section: Discussionmentioning
confidence: 99%
“…Zhan et al (2020) reported three patients with peripheral (Palmer 1B) TFCC injuries and additional ECU pathology but did not study the association between these findings in their small sample [ 4 ]. Verhiel et al (2020) assessed 67 patients with TFCC tears and 67 controls with MRI and arthroscopy, concluding that ECU pathology and distal radioulnar joint arthritis are associated with TFCC tears [ 15 ]. In the most recent work, Kim et al (2021) studied the ECU tendon subluxation with 297 MRI cases; out of these, 111 cases had arthroscopic evaluation of TFCC.…”
Section: Discussionmentioning
confidence: 99%
“…(continued) ,10,38,40,43,49,57,58,66,76,89,101,104,107,111,127,128,[132][133][134]137,146,167,171,172,174,181,182,195,46,48,51,70,71,74,85,95,113,121,124,125,163,173,176,177,180,183,[187][188][189][190][191]201,202 Sex unclear or not reported5-7,9,10,34,38,40,45,50-52,54,55,63,65,67,68,71,73,76,80,81,83,84,88-90,96,98,99,101-103,106,109-111,113, …”
mentioning
confidence: 99%